Pemanfaatan Teknologi Sel Surya untuk Optimalisasi Budidaya Ikan Lele Berbasis Sistem Biofloc-Aquaponic - Sunaryono Sunaryono; Markus Diantoro; Ahmad Taufiq; Hendra Susanto; Muhammad Ikhwan Najmi; Futri Yuliana (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2023)
Gadingkasri Village is one of the villages located in the Klojen District of Malang City which is located in the downtown area of Malang. The location of the village surrounded by a business center and several universities makes this village very strategic because it is a densely populated residential area with a combination of residential communities and students as boarding house residents. With this condition, Gadingkasri Village has considerable economic zone potential for its people. Gadingkasri Village, especially residents in RW. 3, there is a community of PKK mothers who are members of the Urban Farming Group who have a vision to green residential areas by gardening around settlements. One of the potentials that can be developed is to develop community activities in the Urban Farming community towards optimizing energy and increasing residents' income by raising catfish. The community service program through funding from the State University of Malang aims to maximize the existing potential through the use of appropriate technology. The method used in this service is a method of empowering catfish farming by utilizing appropriate technology engineering for sustainable alternative energy. The activities that have been carried out are in the form of mentoring, designing, installing aquaponic systems, and biofloc pools, and solar panels which will be alternative energy in supplying aquaponic pump electrical systems and biofloc ponds. The results of this service activity are expected to be an alternative energy source solution that can be used independently by RW residents. 3 Gadingkasri village. The empowerment of catfish with a biofloc system is also expected to be able to increase the economic income of residents